Peningkatan Kemampuan Guru dalam Penerapan Model Pembelajaran Kooperatif melalui Supervisi Klinis di SD Negeri 2 Masbagik Selatan - Rukanti, Baiq Dewi (Lembaga Yasin AlSys, 2021)
The purpose of this school action research is to determine the improvement of teacher abilities in the application of cooperative learning models through clinical supervision at SD Negeri 2 Masbagik Selatan for the 2020/2021 academic year. Based on the results of the research above, the results of the principal's coaching are very good. This can be seen at the first meeting of the 10 teachers who were present at the time of this study, the completeness of achieving the ideal performance of cycle I and cycle II, respectively, was 33% increasing to 100%. From the analysis of the data above, it can be seen that coaching in improving the ability of teachers to apply learning models through the guidance of the Principal, which means that the teaching and learning process is more successful and can improve its quality, especially at SDN 2 Masbagik Selatan, East Lombok district, therefore it is expected that the teachers of SDN 2 South Masbagik can improve its quality in carrying out classroom learning.